Elaboración de un estudio de prefactibilidad del montaje de una empresa de comercialización, instalación de plataformas piezolectricas: caso estaciones y portales de trasmilenio (2018)
Pre-feasibility study of the application of piezoelectric platforms in Stations and Portals of Transmilenio in the city of Bogotá, as sources of energy generation where the main resource is the users and their footsteps, the study has a general view of the energy issue in Colombia and how renewable energies are making inroads in recent years.